Anti-apoptotic BCL-2 family proteins in acute neural injury - Anilkumar, Ujval; Prehn, Jochen H. M. (Frontiers in Cellular Neuroscience, 2014)
Cell death signaling frequently converges on mitochondria, a process that is controlled by the activities of pro- and anti-apoptotic B-cell lymphoma 2 (BCL-2) proteins. In this review, we summarize current knowledge on the control of neuronal survival, development and injury by anti-apoptotic BCL-2 family proteins. We discuss overlapping and differential effects of the individual family members: BCL-2, BCL-extra long (BCL-XL), myeloid cell leukemia 1 (MCL-1) and BCL2-like 2 (BCL-W) in the control of survival during development and pathophysiological processes such as trophic factor withdrawal, ischemic injury, excitotoxicity, oxidative stress and energy stress. Finally we discuss recent evidence that several anti-apoptotic BCL-2 proteins influence mitochondrial bioenergetics and control neuronal Ca2+ homeostasis independent of their classical role in cell death signaling.